Functional genetic variation in aminopeptidase A (ENPEP): lack of clear association with focal and segmental glomerulosclerosis (FSGS) - Tonna, Stephen (2007)
The aminopeptidase A (APA) ectopeptidase is an integral membrane-bound zinc metalloprotease that cleaves aspartic and glutamic acidic residues from the N-terminus of a number of protein substrates that includes angiotensin II. Angiotensin II, the most vasoactive component of the renin-angiotensin-aldosterone (RAAS) pathway, can contribute to renal disease by causing an increase in arterial blood pressure leading to glomerular injury and fibrosis. APA is expressed in many organs, including the kidney where it localizes mainly to the podocyte cell membrane and brush borders of the proximal tubule cells. Antibodies directed to the APA peptide can induce an acute massive albuminuria in wild type BALB/c mice after intravenous injection. We examined whether variants in the APA encoding gene (ENPEP) are more frequent in individuals with the proteinuric disease focal and segmental glomerulosclerosis (FSGS) compared to control individuals. The ENPEP coding sequence was resequenced in 188 FSGS patients and 48 controls. Genetic variants were further genotyped in 181 individuals without any known kidney disease. We then examined the effect of the non-synonymous coding variants identified on their cell surface APA activity after transfection in COS-1 cells. Several of these ENPEP variants lead to reproducibly altered APA activity. However, we did not see a clear correlation between the presence of a functional ENPEP variant and FSGS. However, the existence of these variants with marked effect on APA activity suggests that both rare and common variation in ENPEP may contribute to the development of renal and hypertensive disorders and warrants further study.